INFLUENCE OF RISK MANAGEMENT PRACTICE ON PERFORMANCE OF MICRO SMALL ENTREPRENEURIAL PROJECTS IN NAIROBI CITY COUNTY, KENYA - NJUE, Nicasio (Advances in Social Sciences Research Journal, 2021)
This study aimed at assessing the influence of risk management practice on the performance of Micro Small Entrepreneurial Projects in Nairobi County Kenya. Pragmatic paradigm guided the study. Correlational survey and cross-sectional survey designs were used. Target population was 350 consisting of 327 entrepreneurs and 23 project managers. Using Krejcie and Morgan table of sample determination, a sample of 186 was reached. Proportionate stratified random sampling was used to select 174 entrepreneurs and 12 project managers. Structured questionnaires and key informant interview guide were use in data collection. The split-half method was used to test the internal stability of the questionnaire and the resultant 0.730 (scale reliability) was tested using Cronbach’s Coefficient Alpha method at the widely-accepted social science cut-off of at least α =0.70. Both descriptive and inferential statistics were used in the data analysis. Hypothesis was tested using F-test at 95% confidence interval. At 5% level of significance, the correlation coefficient between risk management practice and performance of Micro Small Entrepreneurial Projects was r=0.014 for p=0.047<0.05, R square=0.00. This implied that there is no significant relationship between risk management practice and performance of Micro Small Entrepreneurial Project and that risk management practice was a poor predictor of the performance of Micro Small Entrepreneurial Projects. Nonetheless, there is need to integrate risk management practice into the other practices of project management so as to safeguard performance of Micro Small Entrepreneurial Projects